Ketone Bodies Impact on Hypoxic CO2 Retention Protocol During Exercise - Prins, Philip J.; Buxton, Jeffrey D.; McClure, Tyler S.; D’Agostino, Dominic P.; Ault, Dana L.; Welton, Gary L.; Jones, Dalton W.; Atwell, Adam D.; Slack, Macey A.; Slack, Marah L.; Williams, Chloe E.; Blanchflower, Morgan E.; et al. (Frontiers in Physiology, 2021)
Exogenous ketone esters have demonstrated the capacity to increase oxygen availability during acute hypoxic exposure leading to the potential application of their use to mitigate performance declines at high altitudes. Voluntary hypoventilation (VH) with exercise reliably reduces oxygen availability and increases carbon dioxide retention without alterations to ambient pressure or gas content. Utilizing a double-blind randomized crossover design, fifteen recreational male distance runners performed submaximal exercise (4x5 min; 70% VO2 Max) with VH. An exogenous ketone ester (KME; 573 mg·kg−1) or iso-caloric flavor matched placebo (PLA) was consumed prior to exercise. Metabolites, blood gases, expired air, heart rate, oxygen saturation, cognition, and perception metrics were collected throughout. KME rapidly elevated R-β-hydroxybutyrate and reduced blood glucose without altering lactate production. KME lowered pH, bicarbonate, and total carbon dioxide. VH with exercise significantly reduced blood (SpO2) and muscle (SmO2) oxygenation and increased cognitive mean reaction time and respiratory rate regardless of condition. KME administration significantly elevated respiratory exchange ratio (RER) at rest and throughout recovery from VH, compared to PLA. Blood carbon dioxide (PCO2) retention increased in the PLA condition while decreasing in the KME condition, leading to a significantly lower PCO2 value immediately post VH exercise (IPE;p=0.031) and at recovery (p=0.001), independent of respiratory rate. The KME’s ability to rapidly alter metabolism, acid/base balance, CO2 retention, and respiratory exchange rate independent of respiratory rate changes at rest, during, and/or following VH exercise protocol illustrates a rapid countermeasure to CO2 retention in concert with systemic metabolic changes.